P781 Patterns of HIV and STI among transgender women in eastern and southern U.S.: interim baseline findings from the LITE cohort. (14th July 2019) - Wirtz, Andrea; Mayer, Kenneth; Radix, Asa; Gaydos, Charlotte; Poteat, Tonia; Cooney, Erin; Cannon, Christopher; Rodriguez, Allan; Wawrzyniak, Andrew; Schneider, Jason; Haw, Sonya; Beyrer, Chris; et al.
Abstract : Background: Transgender women (TGW) in the U.S. experience a disproportionate burden of HIV and STIs. National HIV/STI surveillance does not report statistics for TGW. We describe the baseline prevalence and characteristics of HIV and STI among a cohort of TGW enrolled across 6 cities in eastern and southern US to-date. Methods: Adult TGW, regardless of HIV status, are recruited and enrolled in a baseline screening visit. Participants complete a socio-behavioral survey, oral HIV screening, urine and self-collected anal and vaginal specimens for Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT) testing, and serum treponemal syphilis testing and rapid plasma reagin (RPR) testing with quantitative RPR titers. Participants with negative HIV antibody test results at baseline and HIV-related risk behaviors are enrolled into the cohort. Results: Enrollment launched in March 2018. As of December 2018, 620 TGW completed baseline. Of these, 30% were identified with HIV at baseline and 63% enrolled into the HIV-uninfected cohort. Forty-percent reported a lifetime diagnosis of any STI. At baseline, 34% of HIV-infected participants and 12% of HIV-uninfected participants had ≥=1 laboratory-confirmed STI. Baseline prevalence among all participants included: 2% rectal GC, 0% urogenital GC, 5% rectal CT, 1% urogenital CT, and 13% active syphilis determined by RPR and treponemal results. None of the 38 participants with self-reported history of vaginoplasty had GC or CT at the neovaginal site. Active syphilis infection was associated with residence in a southern city (aOR: 3.8, 95%CI:1.7–8.6), identification as Black and/or Latinx (aOR: 3.7; 95%CI:1.1–12.7), concern about safety in transit to healthcare (aOR: 1.9; 95%CI:1.1–3.3), and positive baseline HIV antibody test (aOR: 3.1; 95%CI:1.7–5.7). Conclusion: TGW in this 6-city baseline cohort have a high prevalence of HIV and STI. Study findings highlight demographic disparities, high HIV/syphilis co-infection, and barriers related to safety that may impede prompt diagnosis and treatment of STI and HIV in American TGW. Disclosure: No significant relationships.